The light in the piazza, and other Italian tales - Spencer, Elizabeth, 1921-2019 (Banner Books (Jackson, Miss.), 1996)
Elizabeth Spencer is captivated by Italy. Collected in this volume are The Light in the Piazza, which is her signature piece, and six other Italian tales in which her American characters encounter and respond to the mysteries of Italian mores.